Taiwan : beyond the economic miracle - Simon, Denis Fred (New York : M. E. Sharpe, 1992)
Taiwan in the modern world
Keywords: Taiwan -- Economic conditions -- 1975 -- Congresses; Taiwan -- Politics and government -- 1975 -- Congresses; Taiwan -- Relations -- China. -- Congresses; China -- Relations -- Taiwan -- Congresses